Analisis Komparatif Abnormal Return, Trading Volume Activity, Harga Saham Terhadap Stock Split - Novitasari, Dewi; Sari, Dian Anita (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
In this study, aberrant stock returns, trading volume activity, and stock prices of businesses listed on the Indonesia Stock Exchange between 2018 and 2022 are compared with and without the stock split. Purposive sampling was used in this investigation, and data from 39 observation businesses were gathered. For data that is not regularly distributed, the wilcoxon signed rank test is employed as a non-parametric test and the paired sample t-test as a parametric test. Testing 10 days prior to and 10 days following the stock split announcement revealed significant variations in the anomalous stock return and trading volume activity variables, according to the results of the partial testing (Wilcoxon signed rank test). The stock price variable, however, demonstrates that tests conducted 10 days prior to and 10 days following the announcement of the stock split did not significantly differ.